Restoration of sinus rhythm in a late presentation of inferior STEMI complicated by complete heart block with percutaneous coronary intervention - Fakhreddine, Omar; Chaabo, Omar; Khoury, Maurice; Ghazzal*, Ziyad (Journal of Cardiovascular Medicine and Cardiology, 2023)
An 87-year-old female patient presented with a two-day history of the chest and epigastric pain associated with generalized fatigue. She was diagnosed with late presentation inferior ST-elevation myocardial infarction complicated by complete heart block. Given her late presentation, she was not taken to the catheterization laboratory immediately. She was admitted to the cardiac care unit. Transthoracic echocardiography showed an ejection fraction of 55% - 60% with wall motion abnormalities involving the posterior and inferior walls. A coronary angiogram the next day showed a total occlusion of the proximal segment of the RCA. Despite the uncertain benefit, taking into account the complete heart block, the artery was re-canalized with stent placement. She remained in complete heart block with stable hemodynamics. The heart team took the decision with the family to delay the insertion of a permanent pacemaker to maximize the chance of spontaneous recovery. Indeed, three days after coronary revascularization, her rhythm evolved into atrial fibrillation and two days later reverted to sinus rhythm with first-degree AV block and LAFB. She remained in normal sinus rhythm and first-degree AV block at her six months follow-up clinic visit. Data regarding the role of percutaneous intervention in patients presenting with late inferior STEMI and complete heart block is lacking. Our case illustrates the possible therapeutic role of late intervention in restoring sinus rhythm and avoiding the insertion of a permanent pacemaker.